Colonization by Akkermansia muciniphila modulates central nervous system autoimmunity in an ecological context-dependent manner - Peipert, Daniel; Montgomery, Theresa L.; Toppen, Lucinda C.; Lee, Margaret Frances J.; Scarborough, Matthew J.; Krementsov, Dimitry N. (Frontiers in Immunology, 2025)
IntroductionMultiple sclerosis is autoimmune disease of the central nervous system (CNS) in which myelin-reactive immune attack drives demyelination and subsequent disability. Various studies have documented elevated abundance of the commensal gut bacterium Akkermansia muciniphila (A. muciniphila) in people with multiple sclerosis compared to healthy control subjects, suggesting that its elevated abundance may be a risk factor for the development of CNS autoimmunity. However, A. muciniphila is considered beneficial in various other pathological contexts, and recent studies suggest that A. muciniphila may be paradoxically associated with reduced disability and progression in multiple sclerosis. Moreover, experimental modulation of A. muciniphila levels in experimental autoimmune encephalomyelitis (EAE), an autoimmune model of multiple sclerosis, has generated conflicting results, suggesting that the effects of this microbe on CNS autoimmunity could be context-dependent.MethodsTo address this possibility, we generated two distinct microbiome models in C57BL/6J mice, each stably colonized by A. muciniphila or A. muciniphila-free, providing divergent ecological contexts in which A. muciniphila may exert a differential impact. We used EAE, flow cytometry, full-length 16S DNA sequencing, and mass spectrometry to assess the impact of A. muciniphila colonization on neurological outcomes, immune responses, gut microbiome composition, and short-chain fatty acid (SCFA) production, respectively. Dietary intervention was used to assess the functional consequences of differences in gut microbiota metabolic capacity. ResultsWe found that A. muciniphila colonization increased EAE severity only in a specific microbiome context, in conjunction with increased Th17 responses and CNS-infiltrating immune cells. Profiling of gut microbiome composition revealed that A. muciniphila colonization drove a reduction of Clostridia, key producers of SCFAs, specifically in the microbiome model in which A. muciniphila exacerbates EAE. Inferred metagenomic analyses suggested reduced SCFA production in the presence of A. muciniphila, which was confirmed by mass spectrometry. Consistently, provision of high dietary fiber as a substrate for SCFA production suppressed EAE only in the context of the Clostridia-rich microbiome sensitive to A. muciniphila colonization. DiscussionTaken together, our data suggest that the effect of A. muciniphila on CNS autoimmunity is highly dependent on the overall composition of the gut microbiome and suggest that this microbe may contribute to decreased gut SCFA metabolism in multiple sclerosis.